Salicylic Acid from Gandapura Oil as an Inhibitor of Ethylene ‎Biosynthesis in Malus sylvestris L. Mill - Pranowo, Dodyk; Rahima, Desiree Rain; Santoso, Imam (El-Hayah : Jurnal Biologi, 2020)
Local apple production, especially Anna's apples, continues to decline. One of the Causes of the decline in local apple production is due to the disproportionate use of chemicals, which causes ethylene production in plants to increase. The purpose of this study was to examine the effect of salicylic acid on reducing levels of ethylene concentrations in Anna apple plants. This study used a completely randomized design (CRD) with a single factor, namely the treatment of various salicylic acid concentrations (25 ppm, 50 ppm, 100 ppm, 200 ppm). The results showed that salicylic acid was able to reduce the value of ethylene concentration in plants. Provision of salicylic acid concentrations starting at 25 ppm was able to inhibit ethylene biosynthesis by more than 90%. The best results were shown in samples treated with 200 ppm salicylic acid concentration. By using salicylic acid alternatives, farmers are able to save around Rp3,040,400 in costs in one harvest period. The percentage of costs for salicylic acid in one harvest period is 3.39% of the total production costs, while the cost of the import promoter is 7.92% of the total production costs